ASSESSMENT AND COMPARISION OF CERVICAL JOINT POSITION SENSE IN SUBJECTS WITH CHRONIC NECK PAIN vs NORMALS (International Journal of Physiotherapy, 2015)
Background: The abundance of mechanoreceptors in the cervical spine and their central and reflex afferent connections to the vestibular, visual and postural control system suggests that the cervical proprioceptive information provides important somatosensory information influencing postural stability, head orientation and eye movement control. Disturbances to the afferent input from the cervical region is thought to underlie symptoms of dizziness, unsteadiness, visual disturbances and signs of altered postural stability, cervical proprioception and head and eye movement control in people with chronic neck pain. This study aimed to assess and compare cervical joint position sense in subjects with chronic neck pain vs normals.Methods: Total 60 subjects, divided into two groups chronic neck pain group (n=30) (12 males and 18 females with mean age of 40.7 years) and control group (n=30) with age and gender matched normal individuals were assessed for baseline data and demographic variables. Head repositioning accuracy test was used to assess cervical joint position sense in degrees.Results: The difference in the head repositioning error values were found to be extremely significant (p